Фінансовий еквівалент вартості життя: сучасні підходи до оцінювання в Україні - Шевчук, О. О.; Моторя, К. В.; Shevchuk, O.; Motoria, K. (Видавництво Львівської політехніки, 2020)
Обґрунтовано теоретичні та методологічні підходи до оцінювання фінансового еквіваленту вартості середньостатистичного життя (ФЕВЖ) з погляду можливостей їх застосування в Україні. Автори запропонували методику обчислення єдиного еквіваленту, яку можна використати для впровадження справедливих та обґрунтованих стандартів розрахунку компенсацій і матеріальної допомоги як з бюджетів усіх рівнів, так і з соціальних фондів та фондів страхових компаній, а також для стимулювання інвестицій у безпеку, розрахунку ефективності управлінських рішень з огляду на можливості запобігання втратам людського капіталу. Оцінений авторами за запропонованою методикою еквівалент ілюструє загальну оцінку якості життя людини в Україні станом на певну дату, оскільки показує, на яку суму відшкодування чи соціальних гарантій може бути спроможна держава в разі втрати життя громадянина залежно від своїх фінансових можливостей, які формуються внеском кожного громадянина в її економічний за вирахуванням інвестицій держави в людський капітал.

The article presents theoretical and methodological approaches to the estimation of financial equivalent of the human life (FELV) value due to the possibilities of their application in Ukraine, proposes a method of calculating the universal equivalent that can be used to introduce fair and justified standards of calculating compensations and financial aid from all levels of budgets, from social funds and insurance companies’ funds, to stimulate investments in security, to calculate the effectiveness of management decisions in view of the possibility of preventing the loss of human capital. The proposed algorithm of estimation includes: 1) estimation of the amount of person’s annual contribution to the economic potential of the state with the deduction of state investments in human capital, 2) using this estimation as an annual premium in the actuarial calculations under the whole life insurance contracts with payment of FELV in case of death, 3) weighing of the equivalent calculated for a certain age to the share of persons of that age in the age structure of the population of the state and calculating the weighted average FELV for the statistical life in Ukraine. The equivalent estimated by the authors using proposed methodology illustrates the integrated valuation of the quality of life in Ukraine for a given date, as it shows the amount of compensation or social guarantees provided by the state in the event of loss of citizen's life, on the basis of state's financial capabilities, which are formed by the contribution of each citizen to its economic potential, reduced by the government investment in human capital. That is, the main idea of defining the financial equivalent of the human life value – balancing the social goals and needs of society with the financial capacity of the state – was reflected in the proposed methodology.
Financial equivalent of the human life value: modern approaches to evaluation in Ukraine
Keywords: вартість життя; фінансовий еквівалент вартості життя; методологія оцінювання; ife value; financial equivalent of the human life value; evaluation methodology; C13; G22; J17; 368.1; 330.59 (477)